Correction to: The Evolution of Fermented Milks, from Artisanal to Industrial Products: A Critical Review (Fermentation, (2022), 8, 12, (679), 10.3390/fermentation8120679) - Bintsis, Thomas; Papademas, Photis (My University, 2024)
Email Correction In the original publication [1], author Thomas Bintsis wants to change the email to: tbintsis@vet.auth.gr. Text Correction There was an error in the original publication. “Recently, Alraddadi et al., 2023 studied the microbial communities of Kefir grains, and Kefir was evaluated over time using highthroughput amplicon sequencing. It was found that Lb. kefiranofaciens and Lentilactobacillus kefiri consistently dominated Kefir grains, whereas Lc. lactis dominated Kefir [193]. Many other bacteria and yeasts were detected that comprised the minor population of Kefir grains and Kefir. The community composition in the kefir was more variable than in the Kefir grains with the relative abundance of both Lb. kefiranofaciens and Lc. lactis changing over time. The fungal communities of Kefir grains were dominated by Kazachstania turicensis and T. delbruekii, although the ratio between the two varied significantly. These findings suggest that the microbial communities in Kefir grains change over time, highlighting the need for further studies investigating the effect these changes have on the production of flavor and aroma compounds in Kefir [193].” A correction has been made to Section 4: Microbiology of Fermented Milk Products, Paragraph 3: “Recently, Alraddadi et al. studied the microbiota of kefir grains and cow’s milk kefir, using high-throughput amplicon sequencing; greater diversity in the microbial composition in the kefir than in the kefir grains was found, and the relative abundance of the dominant species, that is Lb. kefiranofaciens and Lc. lactis and changes over time were observed [194].”